2011
DOI: 10.1103/physrevstab.14.030702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short pulse generation schemes for a soft x-ray free electron laser

Abstract: In this paper we study the performance of two complementary short pulse generation schemes as applied to a soft x-ray free electron laser. The first scheme, recently proposed by Saldin et al., makes use of a laser pulse consisting of only a few optical cycles to give an energy chirp to a short section of an electron bunch and tapers the main radiator undulator in order to compensate the chirped region. The second scheme investigated takes a low-charge, high brightness electron bunch and compresses it to $1 fs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Ideally, we would perform the experiment to probe electrons scattering from the point of maximum acceleration and zero velocity, which sets the pulse duration of the FEL to less than a femtosecond. Recent developments in free electron laser operations have indeed shown that such short pulse duration in the x ray regime is possible 26 . At present, the temporal synchronization of optical and x ray pulses has been demonstrated at the few fs level 27 , but work to reduce it below to ~1 fs is underway 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, we would perform the experiment to probe electrons scattering from the point of maximum acceleration and zero velocity, which sets the pulse duration of the FEL to less than a femtosecond. Recent developments in free electron laser operations have indeed shown that such short pulse duration in the x ray regime is possible 26 . At present, the temporal synchronization of optical and x ray pulses has been demonstrated at the few fs level 27 , but work to reduce it below to ~1 fs is underway 28 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, many methods have been proposed to generate attosecond-level FEL radiation (see e.g. [62][63][64][65]). Here, we will outline those that we found the most interesting, without claiming to provide a fully exhaustive review of the subject.…”
Section: Brief Overview Of Schemes To Obtain Attosecondlong Radiation...mentioning
confidence: 99%
“…One promising scheme for ultra-short pulse generation is the energy chirp plus tapered undulator scheme [13] and we have studied the implementation on CLARA in some detail [45] following earlier assessment for implementation on the UK's NLS proposal [46]. In this scheme, a few-cycle seed laser is used to modulate the electron beam energy to an amplitude greater than the natural bandwidth of the FEL.…”
Section: Slicing Schemesmentioning
confidence: 99%